Autologous Chondrocyte Implantation Is Not Better Than Arthroscopic Debridement for the Treatment of Symptomatic Cartilage Lesions of the Knee: Two-Year Results From a Randomized-Controlled Trial - Per-Henrik Randsborg, Ph.D., M.D; Jan E. Brinchmann, M.D., Ph.D; Christian Owesen, M.D., Ph.D; Lars Engebretsen, M.D., Ph.D; Thomas Birkenes, M.D; Heidi Andreassen Hanvold, P.T; Jūratė Šaltytė Benth, M.S., Ph.D; Asbjørn Årøen, M.D., Ph.D (Elsevier, 2024)
Purpose: To compare the functional and patient-reported outcome measures after autologous chondrocyte implantation (ACI) and arthroscopic debridement (AD) in symptomatic, isolated cartilage injuries larger than 2 cm2 in patients aged 18 to 50 years. Methods: Twenty-eight patients were included and randomized to ACI (n = 15) or AD (n = 13) and followed for 2 years. The primary outcome was the change in the Knee injury and Osteoarthritis Outcome Score (KOOS) Quality of Life (QoL) subscale. Results: The mean age at inclusion was 34.1 (standard deviation [SD] 8.5) years. There were 19 (68%) male patients. The mean size of the lesion was 4.2 (SD 1.7) cm2. There was a statistically significant and clinically meaningful improvement in patient-reported outcome measures from baseline to 2 years in both groups. The improvement from baseline to final follow-up for the primary endpoint (the KOOS QoL subscale) was larger for the AD group (39.8, SD 9.4) compared with the ACI group (23.8, SD 6.7), but this difference was not statistically significant (P = .17). However, according to a mixed linear model there were statistically significantly greater scores in the AD group for several KOOS subscales at several time points, including KOOS QoL, KOOS pain, and KOOS sport and recreation at 2 years. Conclusions: This study indicates that AD followed by supervised physiotherapy is equal to or better than ACI followed by supervised physiotherapy in patients with isolated cartilage lesions of the knee larger than 2 cm2. The improvement in KOOS QoL score from baseline to 2 years was clinically meaningful for both groups (23.8 points for ACI and 39.8 points AD), and larger for the AD group by 16 points. Level of Evidence: Level I, prospective randomized controlled trial.